Thyroid hormone imbalance and the mechanism by which it causes memory loss - Riaz, Faiza; Javed, Eman; Ali, Maida (International Journal of Scientific Reports, 2024)
Thyroid hormone imbalance is the cause of many cognitive dysfunctions such as memory loss, anxiety and depression. A study conducted by Yu et al suggests that hypothyroidism as well as hyperthyroidism causes depression, anxiety and hippocampal dysfunction in rats. The mechanism of these dysfunctions is not yet completely understood.